Correlated evolution of fish host length and parasite spore size: a tale from myxosporeans inhabiting elasmobranchs - Lisnerová, Martina (2022)
Myxozoa represent a diverse group of microscopic cnidarian endoparasites alternating between invertebrate and vertebrate hosts. Of the approximately 2,600 species described predominantly from teleost fish, only 1.8% have been reported from cartilaginous fishes (Elasmobranchii). As ancestral vertebrate hosts of myxozoans, elasmobranchs may have played an important role in myxozoan evolution, however, they are also some of the largest vertebrate hosts known for this group of parasites. We screened 50 elasmobranchs belonging to nine species and seven families, from various geographical areas, for myxozoan infection. We found a 22% overall prevalence of myxozoans in elasmobranchs and describe five species new to science. We investigated, for the first known time, the evolution of spore size within three phylogenetic clades, Ceratomyxa, Sphaerospora sensu stricto and Parvicapsula. We found that spores from elasmobranch-infecting myxozoans were on average 4.8× (Ceratomyxa), 2.2× (Parvicapsula clade) and 1.8× (Sphaerospora sensu stricto except polysporoplasmic Sphaerospora spp.) larger than those from teleosts. In all analysed clades, spore size was correlated with phylogenetic position. In ceratomyxids, it was further strongly positively correlated with fish body size and habitat depth, independent of cellular composition of the spores and phylogenetic position in the tree. While in macroparasites a host size-correlated increase in parasite size occurs on a large scale and is often related to improved exploitation of host resources, in microscopic parasites size ranges vary at the scale of a few micrometres, disproportionate to the available additional space in a large host. We discuss the ecological role of these changes with regard to transmission under high pressure and an invertebrate fauna that is adapted to deeper marine habitats.